Production of Nanopowders of Metal Oxides Using Pulsed Electron Beam in Low Pressure Gas. (13th September 2012) - Sokovnin, S. Yu.; Il'ves, V. G.
Abstract : The installation for production of metal oxide nanopowders was created. The method involves evaporation of the target by a pulsed-electron beam, condensation of the vapors of the material in a low-pressure gas, and deposition of nanopowders on a cold large-area crystallizer. In a new installation, a higher-power electron gun with a hollow cathode, which ensures the formation of the current pulse of the electron beam with amplitude up to 1 A and a duration of 100  μ s, and a crystallizer of a larger diameter (0.3 m) and length (0.5 m), which makes it possible to decrease the agglomeration, were used. The results of the evaporation of targets made of YSZ, CeGdO x, Zn-ZnO, Al2 O3, and ZnO were presented. Room-temperature ferromagnetism has been observed in YSZ, Zn-ZnO, and Cu(Al)-doped Al2 O3 . The proposed method makes it possible to obtain nanopowders of oxides with a characteristic particle size of 3–5 nm and agglomerates consisting of them 20–600 nm in size, specific surfaces of up 338 m 2 /g, productivity of up to 12 g/h, and a specific power consumption ≥112 (W h)/g.